Modified molybdenum disulfide nano material, preparation method and application

The modified molybdenum disulfide nanomaterials were prepared by solution impregnation, which solved the problems of high prices of platinum catalysts and harsh conditions in the prior art, and obtained better electrocatalytic hydrogen evolution performance and simplified preparation process, which promoted the electrical and electrical Development of catalytic decomposition technology.

CN119287424APending Publication Date: 2025-01-10NORTH CHINA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324287.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the existing electrocatalytic water decomposition technology, the expensive price and scarcity of platinum catalysts limit their application, and the current hydrothermal preparation conditions of modified molybdenum disulfide nanomaterials are harsh, which limits the improvement of its electrocatalytic hydrogen evolution performance.

Method used

Modified molybdenum disulfide nanomaterials were prepared by solution impregnation method. By dispersing molybdenum disulfide powder in an alcohol-water mixture, soluble transition metal salt solution was added dropwise to the stirred state, so that transition metal ions were adsorbed on the edge of molybdenum disulfide crystal , increase the active sites and form a modified molybdenum disulfide nanomaterial with excellent electrocatalytic hydrogen evolution properties.

Benefits of technology

It realizes the acquisition of modified molybdenum disulfide nanomaterials with better electrocatalytic hydrogen evolution performance without high temperature and high pressure, simplifies the preparation process and has a wide range of industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287424A_ABST
    Figure CN119287424A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano materials, and particularly relates to a modified molybdenum disulfide nano material, a preparation method and application. The invention provides a preparation method of a modified molybdenum disulfide nano material, which comprises the following steps: uniformly dispersing molybdenum disulfide powder in an alcohol-water mixed solution, dropwise adding a soluble transition metal salt solution into the alcohol-water mixed solution in a stirring state, stirring, carrying out solid-liquid separation, washing, drying and collecting a solid product. The preparation method provided by the invention is simple and feasible, the modified molybdenum disulfide nano material with more excellent electro-catalytic hydrogen evolution performance can be obtained without adopting high-temperature and high-pressure conditions, the preparation conditions are milder, industrial production is easier to realize, and the preparation method has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and specifically relates to a modified molybdenum disulfide nanomaterial, a preparation method and an application thereof. Background Art

[0002] As society's demand for energy continues to increase, hydrogen energy, as a green energy source, has received widespread attention from countries around the world. Electrocatalytic water splitting technology, as a low-cost means of hydrogen production, has become an important means of hydrogen production due to its sustainability. Electrocatalytic water splitting technology mainly uses electrochemical catalysis to decompose water to produce hydrogen. The catalyst used in the electrochemical catalytic process plays a vital role. At present, the catalyst with the highest hydrogen evolution efficiency in electrocatalytic water splitting technology is platinum catalyst, but due to the high price and scarcity of platinum catalyst, its application is greatly limited.

[0003] Molybdenum disulfide (MoS2) has gradually become a highly-regarded hydrogen evolution catalyst due to its unique two-dimensional structure, adjustable active sites, and easy preparation. However, the number of intrinsic active sites of MoS2 is relatively small, which limits its application in electrocatalytic hydrogen evolution reactions. In order to improve the catalytic activity of MoS2, the hydrothermal method is currently used to modify MoS2 using heterogeneous transition metals to activate more catalytic active sites of MoS2 and improve the performance of electrocatalytic hydrogen evolution. However, the current hydrothermal method mostly involves doping heterogeneous transition metals into the in-plane region of MoS2 nanomaterials, and the hydrothermal method needs to be carried out at high temperature and high pressure, and the reaction conditions are relatively harsh. Summary of the invention

[0004] In view of this, the present invention provides a modified molybdenum disulfide nanomaterial, a preparation method and an application thereof. The modified molybdenum disulfide nanomaterial is prepared by a solution impregnation method, and the preparation method is simpler; compared with the same modified molybdenum disulfide nanomaterial prepared by a hydrothermal method, the modified molybdenum disulfide nanomaterial has a more excellent electrocatalytic hydrogen evolution performance.

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a modified molybdenum disulfide nanomaterial, the steps comprising: a molybdenum disulfide dispersion step: uniformly dispersing molybdenum disulfide powder in an alcohol-water mixture or water to obtain a molybdenum disulfide dispersion;

[0006] The transition metal adsorption step is as follows: dripping a soluble transition metal salt solution into the molybdenum disulfide dispersion in a stirring state, and stirring;

[0007] Solid-liquid separation, washing, drying and collecting the solid product to obtain modified molybdenum disulfide nanomaterials.

[0008] The invention first disperses molybdenum disulfide powder in a mixed solution of alcohol and water, then slowly drops a soluble transition metal salt solution into the mixed solution under stirring, utilizes the electrostatic force and affinity of the molybdenum disulfide powder to the transition metal ions, and uses a solution impregnation method to adsorb the transition metal ions on the edge of the molybdenum disulfide crystal, thereby increasing the active sites on the edge of the molybdenum disulfide. The electrocatalytic hydrogen evolution performance of the obtained modified molybdenum disulfide nanomaterial is better than that of the modified molybdenum disulfide nanomaterial prepared by a conventional hydrothermal method.

[0009] In combination with the first aspect, in the molybdenum disulfide dispersion step, the molybdenum disulfide powder is uniformly dispersed in the alcohol-water mixture by ultrasound; wherein the mass volume ratio of the molybdenum disulfide powder to the alcohol-water mixture is 200g:40-60L.

[0010] Ultrasonic vibration can make molybdenum disulfide more evenly dispersed in the alcohol-water mixture, and ultrasonic vibration for 8 to 12 minutes can ensure that the molybdenum disulfide powder is evenly dispersed.

[0011] Preferably, the mass volume ratio of molybdenum disulfide powder to alcohol-water mixture is 200g:50L.

[0012] Preferably, the alcohol-water mixture is obtained by mixing at least one of methanol, ethanol or n-propanol with water; wherein the volume ratio of alcohol to water is 2 to 4:1.

[0013] Preferably, the volume ratio of alcohol to water is 2 to 3:1, more preferably 2 to 2.5:1.

[0014] In combination with the first aspect, the metal in the soluble transition metal salt solution is selected from at least one of cobalt, nickel, copper, zinc, ruthenium, rhodium or palladium. The soluble transition metal salt is a water-soluble salt of the above metals, including but not limited to cobalt salts, nickel salts, copper salts, zinc salts, ruthenium salts, rhodium salts and palladium salts, such as cobalt nitrate, nickel acetate, copper nitrate, zinc chloride, ruthenium chloride, rhodium chloride or palladium chloride.

[0015] In combination with the first aspect, the concentration of transition metal ions in the soluble transition metal salt solution is 0.5×10 -2 ~1.8×10 -2 mol / L. The transition metal ions in this concentration range can not only ensure that the obtained modified MoS2 nanomaterials have more excellent electrocatalytic hydrogen evolution performance, but also maximize the utilization of transition metal ions.

[0016] In combination with the first aspect, the molar ratio of molybdenum atoms in the molybdenum disulfide powder to transition metal atoms in the soluble transition metal salt is 10:0.5-1.5.

[0017] Preferably, the molar ratio of molybdenum atoms in the molybdenum disulfide powder to transition metal atoms in the soluble transition metal salt is 10:1.

[0018] The second aspect of the present invention provides a modified molybdenum disulfide nanomaterial, on the surface of which transition metal ions are adsorbed.

[0019] The third aspect of the present invention provides an application of the modified molybdenum disulfide nanomaterial in hydrogen evolution by water electrolysis.

[0020] Beneficial effects of the present invention: The preparation method provided by the present invention is simple and feasible, and a modified molybdenum disulfide nanomaterial with better electrocatalytic hydrogen evolution performance can be obtained without using high temperature and high pressure conditions. The preparation conditions are milder, and industrial production is easier to achieve, and the method has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The XRD patterns of the modified molybdenum disulfide nanomaterials and molybdenum disulfide obtained in Examples 1 to 7;

[0022] Figure 2 The XRD patterns of the modified molybdenum disulfide nanomaterials and molybdenum disulfide obtained in Comparative Examples 1 to 7;

[0023] Figure 3 The morphology of the modified molybdenum disulfide nanomaterial obtained in Example 1 is characterized, wherein (a) is a SEM image with a scale of 1 μm, (b) is a SEM image with a scale of 500 nm, (c) is an EDS spectrum of all elements of Co / MoS2, (d) is an EDS spectrum of S elements in Co / MoS2, (e) is an EDS spectrum of Co elements in Co / MoS2, and (f) is an EDS spectrum of Mo elements in Co / MoS2;

[0024] Figure 4 The morphology of the modified molybdenum disulfide nanomaterial obtained in Example 2 is characterized, wherein (a) is a SEM image with a scale of 1 μm, (b) is a SEM image with a scale of 500 nm, (c) is an EDS spectrum of all elements of Ni / MoS2, (d) is an EDS spectrum of S elements in Ni / MoS2, (e) is an EDS spectrum of Ni elements in Ni / MoS2, and (f) is an EDS spectrum of Mo elements in Ni / MoS2;

[0025] Figure 5 The morphology characterization of the modified molybdenum disulfide nanomaterial obtained in Example 3, wherein (a) is a SEM image with a scale of 1 μm, (b) is a SEM image with a scale of 500 nm, (c) is an EDS spectrum of all elements of Cu / MoS2, (d) is an EDS spectrum of S elements in Cu / MoS2, (e) is an EDS spectrum of Cu elements in Cu / MoS2, and an EDS spectrum of Mo elements in Cu / MoS2;

[0026] Figure 6The morphology of the modified molybdenum disulfide nanomaterial obtained in Example 4 is characterized, wherein (a) is a SEM image with a scale of 1 μm, (b) is a SEM image with a scale of 500 nm, (c) is an EDS spectrum of all elements of Zn / MoS2, (d) is an EDS spectrum of S elements in Zn / MoS2, (e) is an EDS spectrum of Zn elements in Zn / MoS2, and (f) is an EDS spectrum of Mo elements in Zn / MoS2;

[0027] Figure 7 The morphology of the modified molybdenum disulfide nanomaterial obtained in Example 5 is characterized, wherein (a) is a SEM image with a scale of 1 μm, (b) is a SEM image with a scale of 500 nm, (c) is an EDS spectrum of all elements of Ru / MoS2, (d) is an EDS spectrum of S elements in Ru / MoS2, (e) is an EDS spectrum of Ru elements in Ru / MoS2, and (f) is an EDS spectrum of Mo elements in Ru / MoS2;

[0028] Figure 8 The morphology characterization of the modified molybdenum disulfide nanomaterial obtained in Example 6, wherein (a) is a SEM image with a scale of 1 μm, (b) is a SEM image with a scale of 500 nm, (c) is an EDS spectrum of all elements of Rh / MoS2, (d) is an EDS spectrum of S elements in Rh / MoS2, (e) is an EDS spectrum of Rh elements in Rh / MoS2, and (f) is an EDS spectrum of Mo elements in Rh / MoS2;

[0029] Fig. 9 The morphology characterization of the modified molybdenum disulfide nanomaterial obtained in Example 7, wherein (a) is a SEM image with a scale of 1 μm, (b) is a SEM image with a scale of 500 nm, (c) is an EDS spectrum of all elements of Pd / MoS2, (d) is an EDS spectrum of S elements in Pd / MoS2, (e) is an EDS spectrum of Pd elements in Pd / MoS2, and (f) is an EDS spectrum of Mo elements in Pd / MoS2;

[0030] Fig.10 The LSV diagrams of the modified molybdenum disulfide nanomaterial, molybdenum disulfide and platinum carbon obtained in Example 1 and Comparative Example 1;

[0031] Fig.11 LSV diagrams of the modified molybdenum disulfide nanomaterial, molybdenum disulfide and platinum carbon obtained in Example 2 and Comparative Example 2;

[0032] Fig.12 LSV diagrams of the modified molybdenum disulfide nanomaterial, molybdenum disulfide and platinum carbon obtained in Example 3 and Comparative Example 3;

[0033] Fig.13LSV diagrams of the modified molybdenum disulfide nanomaterial, molybdenum disulfide and platinum carbon obtained in Example 4 and Comparative Example 4;

[0034] Fig.14 LSV diagrams of the modified molybdenum disulfide nanomaterial, molybdenum disulfide and platinum carbon obtained in Example 5 and Comparative Example 5;

[0035] Fig.15 LSV diagrams of the modified molybdenum disulfide nanomaterial, molybdenum disulfide and platinum carbon obtained in Example 6 and Comparative Example 6;

[0036] Fig.16 LSV diagrams of the modified molybdenum disulfide nanomaterial, molybdenum disulfide and platinum carbon obtained in Example 7 and Comparative Example 7;

[0037] Fig.17 This is a bar chart of the electrocatalytic hydrogen evolution performance of the modified molybdenum disulfide nanomaterials obtained in Examples 1 to 7 and Comparative Examples 1 to 7. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] Example 1

[0040] This embodiment provides a cobalt-modified molybdenum disulfide nanomaterial Co / MoS2, which is prepared by a solution impregnation method, and the steps are as follows:

[0041] 200 mg of MoS2 was dispersed in a mixture of 35 mL of anhydrous ethanol and 15 mL of deionized water, and then ultrasonicated in an ultrasonic cleaner for 10 min to uniformly disperse the MoS2 to obtain a MoS2 suspension containing ;

[0042] Dissolve 52 mg Co(NO3)2·6H2O in 10 mL deionized water. Slowly add the Co(NO3)2·6H2O solution to the MoS2 suspension at a rate of 5 mL / h under stirring. Continue stirring for 8 h after the addition. Then collect the reaction product by centrifugation, wash it thoroughly with deionized water and anhydrous ethanol, and then vacuum dry it at 80 ° C for 12 h to obtain the cobalt-modified molybdenum disulfide nanomaterial Co / MoS2.

[0043] Example 2

[0044] This embodiment provides a nickel-modified molybdenum disulfide nanomaterial Ni / MoS2, which is prepared by a solution impregnation method, and the steps are as follows:

[0045] 200 mg of MoS2 was dispersed in a mixture of 30 mL of anhydrous ethanol and 15 mL of deionized water, and then ultrasonicated in an ultrasonic cleaning machine for 10 min to uniformly disperse the MoS2 to obtain a MoS2 suspension containing ;

[0046] Dissolve 45 mg Ni(CH3COO)2·4H2O in 10 mL deionized water. Under stirring, slowly add the Ni(CH3COO)2·4H2O solution to the MoS2 suspension at a rate of 5 mL / h. Continue stirring for 6 h after the addition. Then collect the reaction product by centrifugation, wash it thoroughly with deionized water and anhydrous ethanol, and then vacuum dry it at 80 ° C for 12 h to obtain nickel-modified molybdenum disulfide nanomaterial Ni / MoS2.

[0047] Example 3

[0048] This embodiment provides a copper-modified molybdenum disulfide nanomaterial Cu / MoS2, which is prepared by a solution impregnation method, and the steps are as follows:

[0049] 200 mg of MoS2 was dispersed in a mixture of 40 mL of anhydrous ethanol and 10 mL of deionized water, and then ultrasonicated in an ultrasonic cleaning machine for 10 min to uniformly disperse the MoS2 to obtain a MoS2 suspension containing ;

[0050] Dissolve 31 mg of Cu(NO3)2 in 10 mL of deionized water. Slowly add the Cu(NO3)2 solution to the MoS2 suspension at a rate of 4 mL / h under stirring. Continue stirring for 4 h after the addition is complete. Then collect the reaction product by centrifugation, wash it thoroughly with deionized water and anhydrous ethanol, and then vacuum dry it at 80 ° C for 12 h to obtain copper-modified molybdenum disulfide nanomaterial Cu / MoS2.

[0051] Example 4

[0052] This embodiment provides a zinc-modified molybdenum disulfide nanomaterial Zn / MoS2, which is prepared by a solution impregnation method, and the steps are as follows:

[0053] 200 mg of MoS2 was dispersed in a mixture of 45 mL of anhydrous ethanol and 15 mL of deionized water, and then ultrasonicated in an ultrasonic cleaner for 10 min to uniformly disperse the MoS2 to obtain a MoS2 suspension containing ;

[0054] Dissolve 22 mg ZnCl2 in 10 mL deionized water, slowly add the ZnCl2 solution to the MoS2 suspension at a rate of 6 mL / h under stirring, and continue stirring for 10 h after the addition is completed. Then collect the reaction product by centrifugation, wash it thoroughly with deionized water and anhydrous ethanol, and then vacuum dry it at 80 ° C for 12 h to obtain zinc-modified molybdenum disulfide nanomaterial Zn / MoS2.

[0055] Example 5

[0056] This embodiment provides a ruthenium-modified molybdenum disulfide nanomaterial Ru / MoS2, which is prepared by a solution impregnation method, and the steps are as follows:

[0057] 200 mg of MoS2 was dispersed in a mixture of 55 mL of deionized water, and then ultrasonicated in an ultrasonic cleaning machine for 10 min to uniformly disperse the MoS2 to obtain a MoS2 suspension containing ;

[0058] 27 mg of RuCl3·3H2O was dissolved in 10 mL of deionized water. Under stirring, the RuCl3·3H2O solution was slowly added to the MoS2 suspension at a rate of 5.5 mL / h. After the addition was completed, stirring was continued for 6.5 h. The reaction product was then collected by centrifugation, fully washed with deionized water and anhydrous ethanol, and then vacuum dried at 80 ° C for 12 h to obtain ruthenium-modified molybdenum disulfide nanomaterial Ru / MoS2.

[0059] Example 6

[0060] This embodiment provides a rhodium-modified molybdenum disulfide nanomaterial Rh / MoS2, which is prepared by a solution impregnation method, and the steps are as follows:

[0061] 200 mg of MoS2 was dispersed in a mixture of 35 mL of anhydrous ethanol and 10 mL of deionized water, and then ultrasonicated in an ultrasonic cleaner for 10 min to uniformly disperse the MoS2 to obtain a MoS2 suspension containing ;

[0062] 27 mg of RhCl3·3H2O was dissolved in 10 mL of deionized water. Under stirring, the RhCl3·3H2O solution was slowly added to the MoS2 suspension at a rate of 4.5 mL / h. After the addition was completed, stirring was continued for 4.5 h. The reaction product was then collected by centrifugation, fully washed with deionized water and anhydrous ethanol, and then vacuum dried at 80 ° C for 12 h to obtain rhodium-modified molybdenum disulfide nanomaterial Rh / MoS2.

[0063] Example 7

[0064] This embodiment provides a palladium-modified molybdenum disulfide nanomaterial Pd / MoS2, which is prepared by a solution impregnation method, and the steps are as follows:

[0065] 200 mg of MoS2 was dispersed in a mixture of 40 mL of anhydrous ethanol and 20 mL of deionized water, and then ultrasonicated in an ultrasonic cleaning machine for 10 min to uniformly disperse the MoS2 to obtain a MoS2 suspension containing ;

[0066] 18 mg PdCl2 was dissolved in 10 mL deionized water. Under stirring, the PdCl2 solution was slowly added to the MoS2 suspension at a rate of 7 mL / h. After the addition was completed, stirring was continued for 9 h. The reaction product was then collected by centrifugation, fully washed with deionized water and anhydrous ethanol, and then vacuum dried at 80 ° C for 12 h to obtain palladium-modified molybdenum disulfide nanomaterial Pd / MoS2.

[0067] Comparative Example 1

[0068] This comparative example provides a cobalt-modified molybdenum disulfide nanomaterial Co@MoS2, which is prepared by a hydrothermal method, and the steps are as follows:

[0069] 1.235g (NH4)6Mo7O 24 (0.001mol), 2.131g CH4N2S (0.021mol) and a surfactant were dissolved in 20mL of deionized water respectively, and the three solutions were mixed after being stirred for 30min each for full dissolution. Then 0.291g of the transition metal-containing ionic compound Co(NO3)2 was added to the mixed solution and stirred evenly. Then the mixed solution containing the transition metal-containing ionic compound was transferred to a polytetrafluoroethylene liner with a capacity of 100mL, and then placed in a high-pressure reactor for full reaction at 190°C for 24h, and then naturally cooled to room temperature, washed with deionized water, and vacuum dried at 80°C for 12h. The product was collected to obtain cobalt-modified molybdenum disulfide nanomaterial Co@MoS2.

[0070] Comparative Example 2

[0071] This comparative example provides a nickel-modified molybdenum disulfide nanomaterial Ni@MoS2, which is prepared by a hydrothermal method. The steps are similar to those of comparative example 1, except that the transition metal-containing ionic compound used is Ni(CH3COO)2·4H2O0.248g.

[0072] Comparative Example 3

[0073] This comparative example provides a copper-modified molybdenum disulfide nanomaterial Cu@MoS2, which is prepared by a hydrothermal method. The steps are similar to those of comparative example 1, except that the transition metal-containing ionic compound used is 0.169 g Cu(NO3)2.

[0074] Comparative Example 4

[0075] This comparative example provides a zinc-modified molybdenum disulfide nanomaterial Zn@MoS2, which is prepared by a hydrothermal method. The steps are similar to those of comparative example 1, except that the transition metal-containing ionic compound used is 0.123 g of ZnCl2.

[0076] Comparative Example 5

[0077] This comparative example provides a ruthenium-modified molybdenum disulfide nanomaterial Ru@MoS2, which is prepared by a hydrothermal method. The steps are similar to those of comparative example 1, except that the transition metal-containing ionic compound used is 0.152 g of RuCl3·3H2O.

[0078] Comparative Example 6

[0079] This comparative example provides a rhodium-modified molybdenum disulfide nanomaterial Rh@MoS2, which is prepared by a hydrothermal method. The steps are similar to those of comparative example 1, except that the transition metal-containing ionic compound used is 0.149 g of RhCl3·3H2O.

[0080] Comparative Example 7

[0081] This comparative example provides a palladium-modified molybdenum disulfide nanomaterial Pd@MoS2, which is prepared by a hydrothermal method. The steps are similar to those of comparative example 1, except that the transition metal-containing ionic compound used is 0.098 g of PdCl3.

[0082] Test Example 1

[0083] X-ray diffraction analysis was performed on the series of modified molybdenum disulfide nanomaterials (represented by M / MoS2 and M@MoS2, respectively) obtained in Examples 1 to 7 and Comparative Examples 1 to 7, and the results were as follows: Figure 1 and Figure 2 shown.

[0084] It can be seen that after the modification of molybdenum disulfide with different components, the (002) diffraction peak position of M / MoS2 and M@MoS2 shifts slightly, the positions of the other crystal planes do not change, and no impurity peaks appear, indicating that the doping of transition metal ions has little effect on the lattice structure of MoS2.

[0085] Test Example 2

[0086] The morphological characteristics of the series of modified molybdenum disulfide nanomaterials (represented by M / MoS2) obtained in Examples 1 to 7 were analyzed by scanning electron microscopy, respectively. Figures 3 to 9 shown.

[0087] Combination Figures 3 to 9 It can be seen that the M / MoS2 obtained by the solution impregnation method presents a clear spherical shape, and the surface of the nanoflower ball is a tightly arranged layered structure. The EDS element spectrum of M / MoS2 shows that S, Mo and the loaded metal elements are evenly distributed on the nanoflower ball, indicating that the metal elements are evenly loaded on MoS2.

[0088] Test Example 3

[0089] The doping elements and molybdenum elements of the series of modified molybdenum disulfide nanomaterials (ie, catalysts) obtained in Examples 1 to 7 and Comparative Examples 1 to 7 were determined by inductively coupled plasma emission spectrometry, and the results are shown in Table 1.

[0090] Table 1 Doping elements and molybdenum content of catalysts corresponding to Examples 1 to 7 and Comparative Examples 1 to 7

[0091] catalyst Molybdenum content / (mol.%) Content of introduced elements / (mol.%) Example 1 <![CDATA[Co / MoS2]]> 33.41 1.26 Comparative Example 1 <![CDATA[Co@MoS2]]> 28.57 4.00 Example 2 <![CDATA[Ni / MoS2]]> 33.96 1.25 Comparative Example 2 <![CDATA[Ni@MoS2]]> 28.98 4.72 Example 3 <![CDATA[Cu / MoS2]]> 33.22 1.06 Comparative Example 3 <![CDATA[Cu@MoS2]]> 27.44 4.11 Example 4 <![CDATA[Zn / MoS2]]> 31.17 0.56 Comparative Example 4 <![CDATA[Zn@MoS2]]> 33.12 4.59 Example 5 <![CDATA[Ru / MoS2]]> 31.86 1.43 Comparative Example 5 <![CDATA[Ru@MoS2]]> 41.61 1.30 Example 6 <![CDATA[Rh / MoS2]]> 38.57 0.40 Comparative Example 6 <![CDATA[Rh@MoS2]]> 25.95 2.56 Example 7 <![CDATA[Pd / MoS2]]> 28.78 2.43 Comparative Example 7 <![CDATA[Pd@MoS2]]> 28.36 2.57

[0092] The modified molybdenum disulfide nanomaterials (i.e., catalysts) obtained in Examples 1 to 7 and Comparative Examples 1 to 7, the platinum-carbon catalysts, and the unmodified molybdenum disulfide were subjected to electrochemical tests using a CHI660E electrochemical workstation, wherein the current density was 10 mA cm -2 The electrolyte used for water decomposition is 1.0M KOH solution (pH=14). Under this condition, the electrocatalytic hydrogen evolution performance of the catalyst was tested. The test results are as follows: Figures 10 to 16 As shown, the electrochemical hydrogen evolution performance comparison diagram of the series of modified molybdenum disulfide nanomaterials obtained in Examples 1 to 7 and Comparative Examples 1 to 7 is shown in Fig.17 shown.

[0093] From Table 1 and Fig.17 It can be seen that the content of the introduced element in the series of modified molybdenum disulfide nanomaterials obtained in Examples 1 to 7 is lower or equivalent to that in the series of modified molybdenum disulfide nanomaterials obtained in Comparative Examples 1 to 7, but the content of the introduced element in the series of modified molybdenum disulfide nanomaterials obtained in Examples 1 to 7 is lower or equivalent to that in the series of modified molybdenum disulfide nanomaterials obtained in Comparative Examples 1 to 7, but the content of the introduced element in the series of modified molybdenum disulfide nanomaterials obtained in Comparative ... -2 The corresponding overpotential under the current density is smaller, and the electrocatalytic hydrogen evolution performance is stronger, which indicates that the molybdenum disulfide nanomaterial prepared by the solution impregnation method provided by the present invention has a higher electrocatalytic efficiency.

[0094] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a modified molybdenum disulfide nanomaterial, characterized in that the steps include: Molybdenum disulfide dispersion step: evenly dispersing molybdenum disulfide powder in an alcohol-water mixture or water to obtain a molybdenum disulfide dispersion; The transition metal adsorption step is as follows: dripping a soluble transition metal salt solution into the molybdenum disulfide dispersion in a stirring state, and stirring; Solid-liquid separation, washing, drying and collecting the solid product to obtain modified molybdenum disulfide nanomaterials.

2. The method for preparing the modified molybdenum disulfide nanomaterial according to claim 1, characterized in that: In the molybdenum disulfide dispersing step, the molybdenum disulfide powder is uniformly dispersed in the alcohol-water mixture by ultrasound; wherein the mass volume ratio of the molybdenum disulfide powder to the alcohol-water mixture is 200g:40-60L.

3. The method for preparing the modified molybdenum disulfide nanomaterial according to claim 1, characterized in that: The metal in the soluble transition metal salt solution is selected from at least one of cobalt, nickel, copper, zinc, ruthenium, rhodium or palladium.

4. The method for preparing the modified molybdenum disulfide nanomaterial according to claim 1, characterized in that: The concentration of transition metal ions in the soluble transition metal salt solution is 0.5×10 -2 ~1.8×10 -2 mol / L.

5. The method for preparing the modified molybdenum disulfide nanomaterial according to claim 1, characterized in that: The molar ratio of molybdenum atoms in the molybdenum disulfide powder to transition metal atoms in the soluble transition metal salt is 10:0.1-1.

5.

6. A modified molybdenum disulfide nanomaterial, characterized in that: Transition metal ions are adsorbed on the surface of molybdenum disulfide.

7. Use of the modified molybdenum disulfide nanomaterial according to claim 6 in hydrogen evolution by water electrolysis.